Catalytic Hydroalkylation of Allenes. (13th November 2017) - Lee, Mitchell; Nguyen, Mary; Brandt, Chance; Kaminsky, Werner; Lalic, Gojko
Abstract: We have developed a catalytic method for the hydroalkylation of allenes using alkyl triflates as electrophiles and silane as a hydride source. The reaction has an excellent substrate scope and is compatible with a wide range of functional groups, including esters, aryl halides, aryl boronic esters, sulfonamides, alkyl tosylates, and alkyl bromides. We found evidence for a reaction mechanism that involves unusual dinuclear copper ally complexes as catalytic intermediates. The unusual structure of these complexes provides a rationale for their unexpected reactivity.